Natural Deep Eutectic Solvents – Solvents for the 21st Century - Paiva, Alexandre; Craveiro, Rita; Aroso, Ivo; Martins, Marta; Reis, Rui L; Duarte, Ana Rita C (ACS sustainable chemistry & engineering, 2014)
Green technology actively seeks new solvents to replace common organic solvents that present inherent toxicity and have high volatility, leading to evaporation of volatile organic compounds to the atmosphere. Over the past two decades, ionic liquids (ILs) have gained enormous attention from the scientific community, and the number of reported articles in the literature has grown exponentially. Nevertheless, IL “greenness” is often challenged, mainly due to their poor biodegradability, biocompatibility, and sustainability. An alternative to ILs are deep eutectic solvents (DES). Deep eutectic solvents are defined as a mixture of two or more components, which may be solid or liquid and that at a particular composition present a high melting point depression becoming liquids at room temperature. When the compounds that constitute the DES are primary metabolites, namely, aminoacids, organic acids, sugars, or choline derivatives, the DES are so called natural deep eutectic solvents (NADES). NADES fully represent green chemistry principles. Can natural deep eutectic solvents be foreseen as the next generation solvents and can a similar path to ionic liquids be outlined? The current state of the art concerning the advances made on these solvents in the past few years is reviewed in this paper, which is more than an overview on the different applications for which they have been suggested, particularly, biocatalysis, electrochemistry, and extraction of new data. Citotoxicity of different NADES was evaluated and compared to conventional imidazolium-based ionic liquids, and hints at the extraction of phenolic compounds from green coffee beans and on the foaming effect of NADES are revealed. Future perspectives on the major directions toward which the research on NADES is envisaged are here discussed, and these comprised undoubtedly a wide range of chemically related subjects.